Morosidad en Mibanco, agencia Trujillo - Sánchez Rivera, José Heli (2019)
The aim of this work is to inform, about the measures taken by Mibanco, by order of the Superintendencia de Banca, Seguros y AFP to support micro-entrepreneurs affected by El Niño phenomenon in the year 2017. The reprogramming of credits made in that period, MANAGED TO reduce the level of arrears problems in the Mibanco Central Office in the city of Trujillo.